Spanish Validation of the Leader Empowering Behavior Questionnaire (LEBQ) - Bonavia, Tomas; Marin-Garcia, Juan A. (Frontiers in Psychology, 2019)
The concept of empowering leadership has attracted widespread academic and practical interest and different questionnaires have been developed to measure it. However, there are no instruments to measure empowering leadership in the Spanish language. This article presents the translation, adaptation, and validation of a scale to measure this construct. In addition, it analyzes the relationship between managers’ empowering leadership and employees’ job satisfaction. In turn, the study analyzes whether employees who participate in a greater number of continuous improvement programs have supervisors who favor more empowering behaviors. A total of 739 participants with various occupations from different companies that have implemented continuous improvement processes filled out the Spanish version of the Leader Empowering Behavior Questionnaire (LEBQ-sp). Two different subsamples were used to test the relationships between the LEBQ and job satisfaction and continuous improvement, by means of Pearson's correlation coefficient and analysis of variance, making it possible to provide evidence about the validity of the Spanish LEBQ. The confirmatory factor analysis supported the original structure of the six-factor model. The factors show a high level of internal consistency, as well as sufficient convergent and discriminant validity. Moreover, the results show that the more companies invest in formal continuous improvement programs, the more important it is for their leaders to adapt their behavior by displaying more empowering leadership. The LEBQ-sp is a valid and reliable instrument for use in research and a useful tool for applied purposes in the context of Spanish-speaking countries.